Chemical and Biological Studies of Leaf Extract of Dendrophthoe falcata Linn. (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Dendrophthoe falcata (Family Loranthaceae) is used extensively in rural area as a component of ethno-medicine for the treatment of various diseases. In this study, the crude extracts and the fractions obtained from D. falcata were investigated for potential chemical constituents and some biological activities. For medicinal properties the antioxidant, brine shrimp lethality and thrombolytic activities have been investigated. The structures of the isolated three compounds were solved by extensive analyses of their high resolution 1HNMR spectroscopic data. They were identified as Lupeol, 3-β-acetoxy-12-ene-11-one and β-sitosterol. For bioactivities, the petroleum ether, dichloromethane, chloroform and aqueous soluble fractions abbreviated as PESF, DCMSF, CSF and AQSF respectively. Brine shrimp lethality bioassay was used to evaluate potential cytotoxic activities, where all fractions showed significant activity with lower LC50. Most significant activity has been observed for methanol extract (LC50= 4.477 µg/ml). AQSF revealed maximum activity in DPPH free radical scavenging assay (IC50 = of 43.49 μg/ml). In assay for thrombolytic activity, the methanol extract and its chloroform soluble fraction demonstrated significant efficacy with 32.65% and 32.36% clot lysis, respectively.Dhaka Univ. J. Pharm. Sci. 16(2): 215-219, 2017 (December)